Petrogenesis and tectonic implications of the early Carboniferous volcanic rocks in West Junggar, NW China. (4th September 2019) - Weng, Kai; Ma, Zhongping; Cao, Kai; Dong, Yunpeng; Chen, Bo; Zhao, Xiaojian
Abstract : Carboniferous magmatism in the Darbut region is critical for understanding the evolutionary history of the accretionary orogenesis of the West Junggar area in the Central Asian Orogenic Belt. In this paper, zircon U–Pb geochronological, whole‐rock geochemical and Sr–Nd–Pb–Hf isotopic analyses of the basalts, basaltic andesite, and dacite from the Carboniferous Tailegula Formation, Darbut region, have been performed. The magmatic zircons from basalt, basaltic andesite, and dacite yield concordia U–Pb isotope ages of 344 ± 4, 347 ± 3, and 340 ± 5 Ma, respectively, which are interpreted as the crystallization ages of these rocks. The basalts and basaltic andesite are characterized by an alkali composition; high Nb/Yb, Th/Yb, Ta/Yb, La/Sm, and Sm/Yb trace element ratios and Pb isotopic ratios; moderate ( 87 Sr/ 86 Sr)i ratios; low ( 143 Nb/ 144 Nb)i ratios; and positive εNd (t) (+0.66 − +4.73) and εHf (t) (+1.7 − +15.2) values. These characteristics indicate that the magmas were derived from mixed mantle sources, that is, enriched mantle sources and high U/Pb ratio mantle (HIMU) component sources with ≤10% partial melting of garnet and spinel lherzolite. The samples display pronounced light rare earth elements (LREEs) and incompatible element enrichment patterns with positive Nb–Ta anomalies and a high Pb content and Nb/La ratios but low (Th/Nb)N ratios and a lower degree of partial melting, implying that these rocks were formed in a continental extensional setting. Based on our results and that of previous studies, we conclude that the early Carboniferous volcanic rocks in the Darbut region formed by mantle plume or regional‐scale mantle upwelling in a continental extensional setting after closure of the Junggar Ocean.